1993
DOI: 10.1103/physrevlett.71.3798
|View full text |Cite
|
Sign up to set email alerts
|

Coherent startup of an infrared free-electron laser

Abstract: Coherent enhancement of the spontaneous undulator radiation by several orders of magnitude has been observed in a free-electron laser at wavelengths from 40 to 100 /im. The coherent emission can be explained by details of the electron-beam micropulse structure. Furthermore, it has been found that the phase of the optical micropulses is fixed by the electron pulse structure and that the coherence extends over successive optical micropulses, which gives rise to interference effects as a function of the optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 7 publications
2
33
0
Order By: Relevance
“…Longer wavelength systems have demonstrated that bunch rise times $10k/c, where c is the speed of light in vacuum, are sufficiently rapid to seed self-amplified coherent spontaneous emission (SACSE) in FELs. 28,29 At k ¼ 150 nm, for example, this corresponds to a threshold rise time $5 fs. For our beam line setup as modelled in Fig.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…Longer wavelength systems have demonstrated that bunch rise times $10k/c, where c is the speed of light in vacuum, are sufficiently rapid to seed self-amplified coherent spontaneous emission (SACSE) in FELs. 28,29 At k ¼ 150 nm, for example, this corresponds to a threshold rise time $5 fs. For our beam line setup as modelled in Fig.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…This large amount of spontaneous emission shown by short beams was first observed in Refs. [22,23], studied then in detail in [18,19,24,25] and connected with the presence of large gradients in the current profile. One could advance a possible alternative explanation of this enhanced spontaneous emission by the following reasoning.…”
Section: Numerical Resultsmentioning
confidence: 98%
“…There are two new candidates for generating high power THz radiation. One is accelerator-based radiation, such as coherent synchrotron radiation [11,12], coherent transition radiation [13], free electron laser [14], Cherenkov radiation [15] and Smith-Purcell effect [16], etc. These facilities can provide a high average power output tunable at a very broad band.…”
Section: Introductionmentioning
confidence: 99%